Relationship of Family Environmental Conditions with Types of Juvenile Delinquency - Ristha Purnama Kario; Susanti Niman; Tina Shinta Parulian (Jurnal Keperawatan Jiwa (JKJ): Persatuan Perawat Nasional Indonesia, 2020)
This study is motivated by the existence of family environment conditions that influence juvenile to do delinquency. The purpose of this study is to find out whether there is a relationship between the condition of the family environment with the type of juvenile delinquency. The sample uses a total sampling of 130 respondents in children's penitentiary. The research method used quantitative, correlational descriptive designs, and cross sectional approaches. The research instrument was in the form of a questionnaire with validity ≥ 0.374 and reliability 0.975. The family environment is the first and foremost education for children. The family is an informal educational institution, no less important than formal institutions, so there are differences in the personality of individuals against a background of family differences. The results of univariate analysis found 81 respondents (62.3%) have good family environment conditions. The results of the chi-square test did not correlate family environment conditions with the type of juvenile delinquency (> 0.05).